2004
DOI: 10.1007/bf03033456
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxins and neurotoxic species implicated in neurodegeneration

Abstract: Neurotoxins, in the general sense, represent novel chemical structures which when administered in vivo or in vitro, are capable of producing neuronal damage or neurodegeneration--with some degree of specificity relating to neuronal phenotype or populations of neurons with specific characteristics (i.e., receptor type, ion channel type, astrocyte-dependence, etc.). The broader term 'neurotoxin' includes this categorization but extends the term to include intra- or extracellular mediators involved in the neurode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 204 publications
0
50
0
Order By: Relevance
“…32,33 Treatment of dopaminergic cells with 6-OHDA elicits robust activation of ERK1/2, and pharmacological inhibition of ERK activation enhances neuronal survival. 34,35 Interestingly, 6-OHDA elicits a delayed phase of mitochondrial ROS production 35 that is associated with increased mitochondrial ERK activation.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Treatment of dopaminergic cells with 6-OHDA elicits robust activation of ERK1/2, and pharmacological inhibition of ERK activation enhances neuronal survival. 34,35 Interestingly, 6-OHDA elicits a delayed phase of mitochondrial ROS production 35 that is associated with increased mitochondrial ERK activation.…”
Section: Introductionmentioning
confidence: 99%
“…Glutamate, the major excitatory neurotransmitter in the brain, is also categorized as an excitotoxin (Segura-Aguilar and Kostrzewa, 2004). Monosodium glutamate (MSG) is used as a food additive, which causes only minor alterations in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays MPP + is believed to be a complex compound acting at different levels in DA neurons (see, for review, Segura Aguilar and Kostrzewa, 2004). In vitro studies with synaptosomes suggested that MPP + enters the cell using DAT (Bougria et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Inside the cell, MPP + binds to complex-I of the mitochondrial respiratory chain, causing the inhibition of NAD-linked mitochondrial respiration (Javitch et al, 1985), an increase in the generation of reactive oxygen species (Akaneya et al, 1995;Jenner, 1998;Przedborski and Vila, 2003;SeguraAguilar and Kostrzewa, 2004) and caspase-3 activation (Du et al, 1997). Recently, it was reported that MPP + may act by other non-DAT dependent mechanisms; thus the precise mechanism of MPP + -induced degeneration is still under discussion (Mytilineou, 2001;Segura-Aguilar and Kostrzewa, 2004).…”
Section: Fp Graham Publishing Comentioning
confidence: 99%